The effectiveness of using graphic novels in the new literature component of the English curriculum on Malaysian secondary school students' literacy / Alia Dzafrina Noorizan - Noorizan, Alia Dzafrina (Faculty of Education, 2014)
This study was carried out to investigate the effectiveness of using graphic novels in the new literature component of the English curriculum in Malaysian secondary school students’ literacy. This is a mixed method of both quantitative and qualitative study that utilizes the use of questionnaires and interview as a method of data collection. A set of questionnaire was designed and distribute to 50 students consists of 19 male and 31 female of Form One students of SMK. Seksyen 9 Shah Alam. An interview also was conducted with the English teacher of the Form One students using a list of open-ended questions. The purposes of conducting this study are to identify the strengths and weakness of using graphic novels in the new literature component of the English curriculum in Malaysian secondary school on students’ literacy as well as the effectiveness of the usage of the graphic novel on students’ literacy. The overall findings of the study indicate that graphic novels is effective in increasing students’ literacy. Majority of the students agreed that graphic novel contain a lot of benefits in enhancing their literacy. Apart from that, this study also highlighted graphic novel weakness in catering the language needs of high proficiency students. It is hoped that this study will create a better understanding in motivating and encouraging both teachers and students in utilizing graphic novels as a tool for enhancing literacy and English language learning developments.